Growth and Yield of Red Chili through the Application of Biochar and Poschar - Valentinus Ordianus Jemail; Yohanes Parlindungan Situmeang; Luh Kartini (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2023)
This study aims to determine the effect of the type of biochar and various doses of poschar and their interactions on the growth and yield of red chili plants. The design used in this study was a factorial randomized block design consisting of 2 treatment factors, namely factor one: type of biochar (B) which consisted of 3 levels, namely: without biochar treatment and with cow biochar and chicken biochar. Second factor: Poschar dose consists of 2 levels, namely: Poschar 0 tons/ha and goat poschar 15 tons/ha. Thus there were 6 treatments and repeated 3 times, so 18 experimental plots were obtained. The interaction between biochar type treatment and poschar dose did not significantly affect all observed variables except stem diameter and the number of productive branches. Biochar treatment significantly affected maximum plant height, stem diameter per plant, number of fruits per plant, and fruit weight per plant, but did not significantly differ on maximum number of leaves, number of productive branches per plant, fruit length per plant, fruit diameter per plant. Poschar treatment had a significant effect on maximum plant height, maximum number of leaves, number of fruits, and fruit weight per plant, but did not significantly affect stem diameter, number of productive branches, fruit length, and fruit diameter per plant. The highest weight of chili fruit was obtained from biochar cow which was 1465.81 g which was significantly different or increased by 63.72% compared to without biochar, which was 895.32 g. The highest fruit weight per plant was obtained in goat poschar application at a dose of 15 tons/ha which was 1440.87 g, significantly different or increased by 42.96% from without poschar which was 1007.90 g. Keywords: Biochar, Compost, Poschar, livestock waste, chili plants.